2022
DOI: 10.1021/acs.chemmater.1c03744
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Alignment of Methylammonium Cations in an Orthorhombic CH3NH3PbCl3 Single Crystal Observed by Polarized Micro-Raman Scattering Spectroscopy

Abstract: To increase their efficiency and improve their chemical stability, hybrid organic–inorganic perovskites (HOIPs) have been studied intensely over the past few years. There are some unresolved issues with the properties of HOIPs, such as the relation between the configuration of methylammonium (MA) ions and their electronic and structural properties. For example, it was theoretically proposed that the change in the bandgap from direct to indirect and/or structural distortion can be caused by a change in the orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…MA + and FA + cations behave similarly in the high-temperature and intermediate-temperature phases, rotating isotropically and reorienting between their preferred orientations, respectively [ 9 , 14 , 15 , 16 , 17 , 18 , 19 ]. In the low-temperature phase, MA + cations still have an ordered three-fold rotational axis [ 17 , 20 ], while the FA + cations are locally disordered, exhibiting a glass-like state in the arrangement of the cations [ 14 ]. In 2D perovskites, large organic cations have greater freedom of motion compared to 3D perovskites and tend to interact with each other by weak intermolecular forces and with the inorganic framework through strong electrostatic interactions [ 5 , 6 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MA + and FA + cations behave similarly in the high-temperature and intermediate-temperature phases, rotating isotropically and reorienting between their preferred orientations, respectively [ 9 , 14 , 15 , 16 , 17 , 18 , 19 ]. In the low-temperature phase, MA + cations still have an ordered three-fold rotational axis [ 17 , 20 ], while the FA + cations are locally disordered, exhibiting a glass-like state in the arrangement of the cations [ 14 ]. In 2D perovskites, large organic cations have greater freedom of motion compared to 3D perovskites and tend to interact with each other by weak intermolecular forces and with the inorganic framework through strong electrostatic interactions [ 5 , 6 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic cations are spectators of the crystalline environment [ 22 , 35 ]. The polarized Raman spectroscopy of organic vibrations could be used to determine the crystal orientation [ 33 ] and the cation movement [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of polar nanoregions under ambient conditions has been debated in MAPbI 3 and MAPbCl 3 . 67,68 In MAPbBr 3 , it was shown that surface reconstruction can lead to polar domains at low temperatures, while the bulk remained nonpolar. 69 Here we show that pressure can be a tool for achieving stable polar domains in bulk MAPbBr 3 at room temperature, which in turn can improve photoconversion efficiency 58,59 in addition to influencing other electronic properties.…”
mentioning
confidence: 99%